STRATEGI LINGKUNGAN BERBASIS MODAL INTELEKTUAL - Sugito Efendi; Eddy Guridno (Universitas Nasional, 2020)
Based on those statistical hipothesis testing result, the human resources management strategy and training would much influenced the level of employees commitment and competency in doing their tasks and responsibilities.. The higher the employees commitment and competency in serving their customer, and the higher the level of customer satisfaction consequently in these the intellectual capital. The level of intellectual capital would significantly influence the company performance, and then determining of the companies profitability.